2014
DOI: 10.7326/m14-0602
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir-Based Treatment Regimens for Chronic, Genotype 1 Hepatitis C Virus Infection in U.S. Incarcerated Populations

Abstract: Background Prevalence of chronic hepatitis C virus (HCV) infection is high among incarcerated persons in the United States. New, short-duration, high-efficacy therapies may expand treatment eligibility in this population. Objective To assess the cost-effectiveness of sofosbuvir for HCV treatment in incarcerated populations. Design Markov model. Data Sources Published literature and expert opinion. Target Population Treatment-naive men with chronic, genotype 1 HCV monoinfection. Time Horizon Lifetime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 53 publications
1
102
0
2
Order By: Relevance
“…Cost effectiveness analyses for treatment of hepatitis C have focused on the potential of treatment to prevent development of cirrhosis as well as to prevent the complications of cirrhosis. 39,[47][48][49] The benefit of curing hepatitis C in this regard has been well established. 1,5,10 It is important to recognize that these cost savings are to the system as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost effectiveness analyses for treatment of hepatitis C have focused on the potential of treatment to prevent development of cirrhosis as well as to prevent the complications of cirrhosis. 39,[47][48][49] The benefit of curing hepatitis C in this regard has been well established. 1,5,10 It is important to recognize that these cost savings are to the system as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Recently, a cost-effectiveness study found that treatment of HCV with SOF for genotype 1 patients was cost-effective for certain incarcerated subpopulations but also acknowledged issues of divided benefits and affordability to the correctional system. 39 Thus, long-term cost-effectiveness may still prove to be unfeasible in the context of fixed correctional health budgets. Given the minimal toxicity of these new therapies, correctional health systems may face difficulty rationalizing treatment deferral on medical grounds, creating a potential financial and liability risk.…”
Section: Introductionmentioning
confidence: 99%
“…Liu és munkatársai fogvatartottaknál vizsgálták a nem kezelés, a peg-IFN+RBV kettős kezelés és ezekhez viszonyítva a boceprevir, illetve sofosbuvir (SOF) hármas kezelés vár-ható kimenetelét, költséghatékonyságát. Számításuk szerint az egyes stratégiák mellett sorrendben 13,12-13,57-14,43-15,18 minőségi életév (QALY) várható, a SOF-kezeléstől várható a dekompezált májcirrhosis (16%) és a hepatocellularis carcinoma (HCC: 9%) előfor-dulásának legnagyobb arányú csökkenése, és ez a kezelés bizonyult legköltséghatékonyabbnak (28 800 USD per QALY) [25]. A DAA hármas kombinációk közül az AbbVie hármas kombináció, illetve Harvoni-kezelés a megfelelő HCV G1/4, illetve G2/3 fertőzött betegeknél az ismert listaárak alapján megtakarítást eredménye-zett a sofosbuvir+simeprevir, illetve sofosbuvir+ribavirin kombinációkhoz képest [26].…”
Section: Táblázatunclassified
“…These highly effective treatment regimens improve sustained virologic response rates to well over 90 % among chronically HCV-infected patients, though their price can exceed $50,000 per patient. Despite findings that such treatments offer good value [1][2][3], their high price challenges the affordability of their delivery to all eligible patients. It is estimated that there are more than 3 million free-living people in the USA with chronic HCV infections as well as nearly 1 million incarcerated or institutionalized people with such infections [1,4].…”
mentioning
confidence: 99%
“…Combined with the higher perpatient costs, the total potential expenditures to treat all eligible individuals are now estimated in the hundreds of billions of dollars [1,2]. Who is likely to pay?…”
mentioning
confidence: 99%